Histological And Clinical Study On Effects Of Follicular Fluid And B. Serra ta On Achilles Tendon Healing In Dogs (Indian Journal of Animal Production and Management, 2025)
Background: Tendons are strong connective structures that link muscles to  bones, facilitating mobility and stability within the musculoskeletal system.  Tendon injuries exhibit a characteristically slow and often incomplete healing  process. Objectives: the objective of this research was to an evaluate and a  compare efficacy of Boswellia serrata extract and bovine follicular fluid on the  clinical and histological healing of Achilles tendon defects in a canine model. Methods: Twenty-seven adult local dogs were used in this study. A core  lesion defect was surgically induced in Achilles tendon of all animals. The  dogs were divided randomly to three equal groups (n=9): A Control Group,  where the defect was treated with Autologous PRF alone; Treated Group 1  (B.S. Group), treated with 1.5 mL of B. serrata extract and Autologous PRF;  and Treated Group 2 (FF Group), treated with 1.5 mL of bovine follicular  fluid and Autologous PRF. The healing process was monitored for 60 days and  assessed via macroscopic clinical evaluation (lameness, swelling, redness),  and histopathological examination (at days 14, 30, and 60) post-surgery.  Results: Clinically, the B.S. group showed the most rapid improvement, with  a significant reduction in lameness by (day 9) post-surgery compared to the  FF and the control groups. Histopathologically, both treatment groups showed  an absence of inflammation at day 14, unlike the control group. At day 60,  the FF group demonstrated superior tissue regeneration, characterized by the  complete restoration of the tendon’s structural normality with highly organized  regular collagen fibers. Conclusion: Both Boswellia serrata extract and bovine  follicular fluid accelerate the healing of Achilles tendon defects when combined  with PRF. Boswellia serrata provides faster clinical recovery and stimulates  early collagen synthesis, while bovine follicular fluid promotes superior long term structural and histological restoration of the tendon tissue.
Keywords: Tendon; Achilles tendon; Boswellia serrata; Bovine follicular fluid; Dog